Learning at the Right Level (TaRL) with the Help of Learning Media: Impact on Students' Mathematics Learning Outcomes - Gilang Eko Setyo Suharjono; Harianingsih; Ellianawati; Decky Avrilianda (Universitas Pendidikan Ganesha, 2025)
Mathematics learning is often considered complex by students, leading to low learning outcomes due to limited understanding of the material and a lack of active engagement. This study aims to analyze various studies on the Teaching at the Right Level (TaRL) approach assisted by learning media on students' mathematics learning outcomes in the 2020-2025 period. The research method is a Systematic Literature Review (SLR). Data collection was conducted using the Publish or Perish software through the application of the PRISMA protocol. A total of 13 articles have met the inclusion criteria from the initial 500 articles obtained. The results show that this approach significantly improves students' mathematics learning outcomes. Students who receive learning tailored to their level of understanding through interactive media show higher improvements in understanding basic mathematical concepts compared to students who follow conventional learning. TaRL allows teachers to group students based on their actual ability level, rather than by age class, so that learning interventions are more focused and effective. In conclusion, the TaRL approach has shown a positive impact in improving students' mathematics learning outcomes through the assistance of learning media. This study provides in-depth insights for teachers regarding the need to design learning by considering student abilities and utilizing learning media appropriately to optimize learning outcomes.